2008
DOI: 10.1097/brs.0b013e31816c8af7
|View full text |Cite
|
Sign up to set email alerts
|

Full-Endoscopic Interlaminar and Transforaminal Lumbar Discectomy Versus Conventional Microsurgical Technique

Abstract: The clinical results of the full-endoscopic technique are equal to those of the microsurgical technique. At the same time, there are advantages in the operation technique and reduced traumatization. With the surgical devices and the possibility of selecting an interlaminar or posterolateral to lateral transforaminal procedure, lumbar disc herniations outside and inside the spinal canal can be sufficiently removed using the full-endoscopic technique, when taking the appropriate criteria into account. Full-endos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
620
2
40

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 746 publications
(736 citation statements)
references
References 110 publications
20
620
2
40
Order By: Relevance
“…The author report for a far lateral and intralaminar full endoscopic procedure 28 and 29 min [31,33]. For a randomised controlled trial the same authors report for standard microdiscectomy an OR time of 43 min and for a full endoscopic procedure of 22 min [34]. The large number of cases in the studies indicates a very broad experience with this procedure.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The author report for a far lateral and intralaminar full endoscopic procedure 28 and 29 min [31,33]. For a randomised controlled trial the same authors report for standard microdiscectomy an OR time of 43 min and for a full endoscopic procedure of 22 min [34]. The large number of cases in the studies indicates a very broad experience with this procedure.…”
Section: Discussionmentioning
confidence: 98%
“…Operation duration was chosen as primary endpoint e, as it is an objective parameter in order to perform a sound case number estimation using the results of our preliminary studies and results of recently published data comparing minimal invasive procedures to the conventional microsurgical technique [4,13,34].…”
Section: Methodsmentioning
confidence: 99%
“…[6][7][8] Such procedures are now routinely performed on patients under sedation or local anaesthesia. 9 Four randomized or quasi-randomized trials [10][11][12][13] showed that patients treated endoscopically were more likely to return to work (95% versus 72%), returned earlier (25 days versus 49 days) and had a shorter duration of postoperative disability with less need for analgesia than those treated using Spine surgery-approach size does matter…”
Section: Correspondencementioning
confidence: 99%
“…Gibson and Waddell [2] refer to the SCIATICA-Med Trial [3, 4] and a German health technology assessment report [5] identified three RCTs and 12 case series between 1998 and 2004 focusing on endoscopically assisted minimally invasive disc surgery. None of these is duplicated in the Nellensteijn review and, most interestingly, a former review with the same title and group of authors funded by the Dutch Health Care Insurance Board, yielded 8 controlled studies and 31 cohort studies [6].The 2010 Nellensteijn review has also omitted three key publications on the grounds of lacking focus on lumbar stenosis [7][8][9] and data from several observational studies focusing on foraminal treatment access [10][11][12][13][14][15]. These data should at least have been referred to when considering the potential effectiveness of transforaminal endoscopic surgery in a full text evaluation.…”
mentioning
confidence: 99%
“…The 2010 Nellensteijn review has also omitted three key publications on the grounds of lacking focus on lumbar stenosis [7][8][9] and data from several observational studies focusing on foraminal treatment access [10][11][12][13][14][15]. These data should at least have been referred to when considering the potential effectiveness of transforaminal endoscopic surgery in a full text evaluation.…”
mentioning
confidence: 99%